Psycho [videorecording (DVD)] - Hitchcock, Alfred, 1899-1980; Perkins, Anthony, 1932-1992; Miles, Vera; Leigh, Janet; Bloch, Robert, 1917-1994 (Alfred Hitchcock collection., 1998)
Horror melodrama in which a woman disappears after spending the night in an isolated motel which adjoins an eerie Victorian mansion, inhabited by a disturbed young man and his mother.